Immunotherapy in the First-Line Treatment of NSCLC: Current Status and Future Directions in China - Xiong, Anwen; Wang, Jiali; Zhou, Caicun (Frontiers in Oncology, 2021)
Lung cancer causes significant morbidity and mortality in China and worldwide. In China, lung cancer accounts for nearly one-fourth of all cancer deaths. Non-small cell lung cancer (NSCLC) is the predominant type of lung cancer, accounting for approximately 80%–85% of all lung cancer cases. Immunotherapy with immune checkpoint inhibitors (ICIs) is revolutionizing the treatment of NSCLC. Immune checkpoint molecules, including PD-1/PD-L1 and CTLA-4, can suppress immune responses by delivering negative signals to T cells. By interfering with these immunosuppressive axes, ICIs unleash antitumor immune responses, ultimately eliminating cancer cells. ICIs have demonstrated promising antitumor efficacy in NSCLC, and mounting evidence supports the use of ICIs in treatment-naïve patients with advanced NSCLC. A comprehensive overview of current and emerging ICIs for the first-line treatment of NSCLC in China will facilitate a better understanding of NSCLC immunotherapy using ICIs and optimize the clinical use of ICIs in previously untreated Chinese patients with NSCLC. Herein, we review the efficacy and safety of currently approved and investigational ICIs as the first-line treatment of NSCLC in China. We also discuss the challenges limiting more widespread use of ICIs and future directions in the first-line treatment of NSCLC using ICIs.